2020
DOI: 10.1111/1749-4877.12425
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent responses of food‐hoarding to competitors in Apodemus peninsulae: implications for coexistence among asymmetrical species

Abstract: Superior species may have distinct advantages over subordinates within asymmetrical interactions among sympatric animals. However, exactly how the subordinate species coexists with superior species is unknown. In the forests west of Beijing City, intense asymmetrical interactions of food competition exist among granivorous rodents (e.g. Apodemus peninsulae, Niviventer confucianus, Sciurotamias davidianus and Tscherskia triton) that have broadly overlapping habitats and diets but have varied body size (range 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 49 publications
4
37
0
Order By: Relevance
“…The plasticity of food hoarding strategies of rodents according to food abundance may partially explain the U‐shaped change of seed dispersal distance (Niu et al . 2020). Rodents appear to move seed further for hoarding to reduce competition and pilferage when seed abundance is relative low, and they tend to rapidly cache seeds around the sources to maximize food harvest when seed production is high and ephemeral (Jenkins & Peters 1992; Galvez et al .…”
Section: Discussionmentioning
confidence: 99%
“…The plasticity of food hoarding strategies of rodents according to food abundance may partially explain the U‐shaped change of seed dispersal distance (Niu et al . 2020). Rodents appear to move seed further for hoarding to reduce competition and pilferage when seed abundance is relative low, and they tend to rapidly cache seeds around the sources to maximize food harvest when seed production is high and ephemeral (Jenkins & Peters 1992; Galvez et al .…”
Section: Discussionmentioning
confidence: 99%
“…The cached foods of hoarders are often pilfered by intraor inter-specific competitors, which threaten the survival and reproduction of the hoarders (Vander Wall & Jenkins 2003;Gu et al 2017). Accordingly, food hoarders have evolved different strategies to reduce pilfering of their caches and replace lost caches by harvesting food from the source and/or pilfering caches from other hoarders (Vander Wall & Jenkins 2003;Dally et al 2006;Niu et al 2020a). Due to differences in hoarding behaviors (larder hoarding vs. scatter hoarding), ability to protect caches, and pilferage among sympatric animals, the results showed that the competition are usually asymmetric, in that some species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…small-sized species) (Vander Wall et al 2009;Penner & Devenport 2011;Zhang et al 2014a;Dittel et al 2017). Under the asymmetric interactions of food competition, competitive strategies of the subordinate species are considered in understanding species coexistence, but they are not yet fully understood (Niu et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Gu et al (2017) and White et al (2017) investigated the relationships between rodents and seeds at the individual level combining infrared radiation camera tracking and seed tagging. Although these methods have been used in many ecosystems for tracking seed dispersal, the main shortcoming is the influence of seed alteration on either seed choice by animals or the following seedling establishment (Levey and Sargent, 2000;Godoy and Jordano, 2001;Tewksbury et al, 2002;Hirsch et al, 2012a,b;Yi and Wang, 2015;Niu et al, 2020). Xiao and Zhang (2003) have well compared a majority of tracking methods, pointing out their advantages and limitations and potential implications in seed dispersal ecology.…”
Section: Introductionmentioning
confidence: 99%